Analysis of the Trade Relations Between the Republic of Macedonia and the Federal Republic of Germany - Emilija Miteva-Kacarski; Iskra Stanceva-Gigov; Kostadinka Cabuleva (Economic Review: Journal of Economics and Business, 2015)
Foreign trade represents an important factor for the economic development of a single country and a basic element in the system of forms through which the openness of the economy is being realized. Taking into account the fact that the Federal Republic of Germany (FRG) is the most important foreign trading partner of the Republic of Macedonia (RM), the paper brings an analysis of the value, dynamics and structure of the foreign trade between RM and FRG for the time period of 2001-2013. It also analyzes the competitiveness of Macedonian products on the German market so that the product categories having a comparative advantage can be determined. The results of the analysis point to the fact that in the past few years the RM has realized a trade surplus in the exchange with FRG as a result of the catalyst export of bearers of precious metals and their compounds, the product category which brings the country a comparative advantage in the exchange with FRG.
Keywords: F14; 330; comparative advantage; Republic of Macedonia; Federal Republic of Germany